2012
DOI: 10.1093/ndt/gfs491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Chronic Kidney Disease Epidemiology Collaboration equation for estimating glomerular filtration rate in the Chinese population

Abstract: The CKD-EPI two-level race equation and the Chinese equation performed similarly in the Chinese population, and both performed better than the MDRD Study equation and the CKD-EPI four-level race equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 24 publications
2
134
0
Order By: Relevance
“…Our study is also one of the first to relate varying lipid parameters to kidney disease using the novel CKD-EPI equation, which is as accurate as the MDRD Study equation at GFR<60 ml/min/1.73 m 2 but is more accurate at higher GFRs [17]. Moreover, a recent multicenter study of 977 Chinese participants, including healthy adults and CKD patients, indicated that the CKD-EPI equation performed better than the MDRD Study equation, with less bias, improved precision and greater accuracy [27]. The prevalence of CKD in our study was 3.7%, and our previous study indicated the prevalence of CKD was 9.0% in hypertensive subjects [28], which is lower than that in participants from Beijing [29], partly because of the younger age and better socioeconomic status of our present patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is also one of the first to relate varying lipid parameters to kidney disease using the novel CKD-EPI equation, which is as accurate as the MDRD Study equation at GFR<60 ml/min/1.73 m 2 but is more accurate at higher GFRs [17]. Moreover, a recent multicenter study of 977 Chinese participants, including healthy adults and CKD patients, indicated that the CKD-EPI equation performed better than the MDRD Study equation, with less bias, improved precision and greater accuracy [27]. The prevalence of CKD in our study was 3.7%, and our previous study indicated the prevalence of CKD was 9.0% in hypertensive subjects [28], which is lower than that in participants from Beijing [29], partly because of the younger age and better socioeconomic status of our present patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…AKI was defined and staged according to the Kidney Disease: Improving Global Outcomes criteria (24). Estimated glomerular filtration rate (eGFR) was calculated by the Chronic Kidney Disease Epidemiology Collaboration equation and is expressed as milliliters per minute per 1.73 m 2 (25). Patients were scheduled for monthly follow-ups for 6 mo and then every 3 mo until at least 1 y after renal biopsy.…”
Section: Patientsmentioning
confidence: 99%
“…Definition of CKD Serum creatinine (Scr) was measured by Jaffe's kinetic method and was standardized at the central laboratory to a national reference. Estimated glomerular filtration rate (eGFR) was calculated using the following estimating equation, which was developed by modifying the Modification of Diet in Renal Disease equation based on the data from Chinese CKD patients: eGFR (mL/min/1.73 m 2 ) = 175 × Scr (mg/dL) -1.234 × age (year) -0.179 (female × 0.79) [17,18]. Reduced renal function was defined as an eGFR < 60 mL/min/1.73 m 2 .…”
Section: Methodsmentioning
confidence: 99%